Heterogeneous distribution of Culex pipiens, Culex quinquefasciatus and their hybrids along the urbanisation gradient - Cardo, María Victoria (2018)
The mosquitoes of the Culex pipiens complex, hereafter referred to as the Pipiens Assemblage, are vectors of arbovirus of worldwide concern including West Nile and St. Louis encephalitis. Given their distinct eco-physiology and vectorial capacity, accurate specimen identification and insight in the environmental drivers of their distribution are essential for the understanding of disease transmission patterns. Using a PCR-based identification protocol, we characterized the spatial distribution of Cx. pipiens, Cx. quinquefasciatus and their hybrids developing in used tyres located within the overlapping region in South America as a function of different estimators of the urbanisation gradient. Out of 84 samples collected from tyre piles of 20 sites, we identified 369 larvae which corresponded predominantly to Cx. quinquefasciatus (76.4% of immatures) all along the gradient but more frequent at the urban end. Cx. pipiens (21.4%) was more conspicuous at the low urbanised end but was also present in highly urbanised sites, whereas hybrids were collected in very low numbers (2.2%). The urbanisation estimator best associated with the heterogeneous occurrence of the Pipiens Assemblage members was the proportion of impervious surface 1 km around each tyre pile, which explained 41.7% of the variability in the data, followed closely by the distance to the Capital City (38.3%). Cumulative annual precipitation, population number in a 1 km radius around each pile and distance to the de la Plata River were significantly associated with the distribution of the Pipiens Assemblage at lower explanation percentages (20–23%). A thorough understanding of the ecological basis and environmental associations of the distribution of Pipiens Assemblage members will enable forecasting population trends in changing environments to develop effective control measures for mosquitoes and the diseases they transmit.